Breakthrough coronavirus disease 2019 infection among health-care workers at a tertiary care center in Chitradurga district - Vijayalaxmi Mangasuli; Bhagyalaxmi Sidenur; A M Amrutha; M Sudharani; S B Vijeth (MRIMS Journal of Health Sciences, 2023)
Background: Coronavirus disease 2019 (COVID-19), caused by Severe Acute Respiratory Syndrome Corona Virus 2 (SARS-CoV-2), spread rapidly leading to a pandemic in March 2020. To combat this, the COVID-19 vaccination drive was conducted in India and had its first recipients as the health-care workers who represent a high-risk population for the same. It included both Covishield and Covaxin. This study draws attention to the COVID-19 attack rate among health-care workers in a teaching Medical hospital, Basaveshwara Medical College and Hospital, in Chitradurga, Karnataka, India. Objective: The objective of the study was to assess breakthrough COVID-19 infection after vaccination among health-care workers. Methodology: A cross-sectional study was carried out in Basaveshwara Medical College and Hospital in October 2021 and December 2021. The study participants were more than 18 years old. The participants include BMCH staff including doctors, nurses, watchman, and ward boys. A sample size of 200 was obtained. Results: Most of the sample lies in the age group of 18–30 years, consisting of more females than males. 191/200, i.e., 95.5% of the population have been vaccinated against COVID-19, of which 69.5% have taken Covishield vaccine and 26% have Covaxin vaccine. Only 9/200 tested positive for COVID-19, postvaccination, whereas 2/200 were hospitalized for complications of COVID-19, postvaccination. Conclusion: Breakthrough COVID-19 among BMCH staff members shows that the vaccination has reduced COVID-19 infection.